Growth and mineral nutrition of field crops - Fageria, N. K. , 1942-; Baligar, Virupax C.; Jones, C. Allan (Boca Raton, Florida : CRC Press/Taylor & Francis Group, 2011)
"This new edition of a bestseller examines plant nutrition's role as one of the most important limiting factors that must be overcome to optimize food production.Extensively revised and update, the edition provides comprehensive coverage of on topice such as genetics, physiological and agronomic bases of crop growth.It covers soil-plant-climatic relationship that govern the growth and mineral nutrition of crops in temperature and tropical region. The book contains two new chapters covering remediation of heavy metal contaminated soils and cover crops as well as several new figures, references, and tables"
1. Field crops and mineral nutrition -- 2. Factors affecting production of field crops -- 3. Nutrient flux in soil-plant system -- 4. Diagnostic techniques for nutritional disorders -- 5. Nutrient management of degraded soils -- 6. Remediation of heavy metal contaminated soils -- 7. The effects of essential nutrients on plant diseases -- 8. Wheat and barley -- 9. Rice -- 10. Corn -- 11. Sorghum -- 12. Soybean -- 13. Common bean and cowpea -- 14. Peanut -- 15. Sugarcane -- 16. Cassava and potato -- 17. Cotton -- 18. Forage -- 19. Cover crops
Includes bibliographical references and index
Keywords: Field crops -- Growth; Field crops -- Nutrition